Republic of Madagascar : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
This mission's goal was to have the Malagasy authorities adopt the methodology of the Government Finance Statistics Manual (GFSM) 2014 for their own needs. The desired outcome of adopting the manual is to develop a set of government finance statistics (GFSs) that are consistent with current international standards in order to conduct a macroeconomic analysis of government finance.